Academic Vocabulary and Technology: Academic Vocabulary and Technology - Xoliqov, Farxod (Maktabgacha taʼlim jurnali, 2021)
In the XIX century, as modern technologies have improved well, they have already entered people’s life and they can not imagine their life without technologies. As a consequence, they are widely used in educational establishments also. There are electronic devices such as computers, laptops, iPads in most classrooms now and learners can download content and study it on their devices at any time.